Effect of Controlled Release Antimicrobial-coated Active Packaging on Postharvest Quality of Cherry Tomato Fruit - Baoan LIU; Ying LI; Yao CHEN; Bihong FENG; Yuan SUI; Xiaodi XU; Shuzhi YUAN; Xiaozhen YUE; Jinhua ZUO; Qing WANG (Shipin gongye ke-ji)
Objective: To develop an active packaging system with controlled-release antimicrobial properties and evaluate its effectiveness in preserving cherry tomatoes during storage and transit. Methods: Two antimicrobial coatings were prepared: A 0.5% (W/V) 2,3-butanedione solution and a 1.0% (W/V) β-violet ketone microcapsule solution. These were combined and uniformly applied to the interior of plant-based packaging, then air-dried before use. The packaged cherry tomatoes were monitored for various quality indices. Results: The treated group (T) had a 25% lower decay rate compared to the control (CK) group. After 12 days of storage, treated fruits exhibited delayed softening and color change, with a soluble solids content of 6.8%, vitamin C content of 131.77 mg/100 g, total phenolic content of 1.97 mg/g, flavonoid content of 1.06 mg/g, and a DPPH free radical scavenging rate of 81.36%. Additionally, the activities of antioxidant enzymes, including catalase (CAT), peroxidase (POD), and superoxide dismutase (SOD), were sustained at higher levels. Conclusion: The use of controlled-release antimicrobial coated active packaging significantly enhances the storage quality and shelf life of cherry tomatoes, providing a viable solution for the preservation and transportation of perishable produce.